A Large Sarcophagus from Myrmekion. On Understanding of the Semantic of the Imagery - Vinogradov, Iurii A. (Actual Problems of Theory and History of Art, 2015)
A large marble sarcophagus from Myrmekion (180–190 AD) has a rich décor: sculptured couple is presented on the lid, while scenes from Achilles’ life story are depicted at three panels. It might be supposed that the décor of the sarcophagus represents some kind of joint system — both picturesque and semantic. Main elements of the system are: “the education of Achilles” (the right panel), his “concealment” on Scyros or “the symbolic death” of the hero (the left panel), and his “rebirth” to new heroic life (the front panel). The principal idea of this composition lies in the representation of “the rebirth”, and is connected not with the famous hero only, but with the real person buried in the sarcophagus. Reliefs on the back panel are not just simple decorations but signs of some magic land (paradise) prepared for a human being after his death.